2007
DOI: 10.1002/chem.200601243
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Trigeminal Tricationic Ionic Liquids

Abstract: Novel trigeminal tricationic ionic liquids (TTILs) have been successfully synthesized in high yields by means of Menschutkin quaternization via an S(N)1 mechanism. This reaction presents a new convenient method for transforming glycerol into multifunctional compounds. The physical properties of a series of TTILs were characterized by using a variety of techniques. The prepared salts were tested for antimicrobial activity. Electrochemical characterization of TTILs was also performed, which allowed the estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 36 publications
0
63
0
Order By: Relevance
“…In fact only recently, have specific ILs with biologically active ions been prepared and shown to retain their biological activity; specifically, IL salts of anti-bacterial quaternary ammonium cations were shown to be active against various types of bacteria and in some cases, an increased anti-bacterial effect was observed. [63][64][65][66] But ILs are composed of a minimum of two ions (a cation and an anion) and both may impart biological activity to the resulting salt. This dual functionality inherent in ILs is rarely exploited, 67,68 and we have only recently published our first paper with the designed incorporation of two biologically active ions into an IL.…”
Section: Ionic Liquids As Active Pharmaceutical Ingredients (Apis)mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact only recently, have specific ILs with biologically active ions been prepared and shown to retain their biological activity; specifically, IL salts of anti-bacterial quaternary ammonium cations were shown to be active against various types of bacteria and in some cases, an increased anti-bacterial effect was observed. [63][64][65][66] But ILs are composed of a minimum of two ions (a cation and an anion) and both may impart biological activity to the resulting salt. This dual functionality inherent in ILs is rarely exploited, 67,68 and we have only recently published our first paper with the designed incorporation of two biologically active ions into an IL.…”
Section: Ionic Liquids As Active Pharmaceutical Ingredients (Apis)mentioning
confidence: 99%
“…Indeed ILs of large quaternary ammonium cations such as benzalkonium ([BA] þ ) and didecyldimethylammonium ([DDA] þ ) are known to form ILs and to retain their anti-microbial properties. 63 The cations of lidocaine and ranitidine also appear to have characteristics favorable for IL formation. The anions of docusate, ibuprofen, colawet MA-80, and sulfacetamide, are all FDA-approved compounds for use in pharmaceutical or agricultural applications.…”
Section: A Few Ionic Liquid-api Examplesmentioning
confidence: 99%
“…In a recent study, Pernak and co-workers tested a range of trigeminal tricationic ionic liquids for antimicrobial activity (Pernak et al, 2007b), it was found that, in addition to their broad spectrum antimicrobial activity, their potency was much better than the commercially available benzalkonium chloride. A further study on chiral ammonium-based ionic liquids (Pernak & Feder-Kubis, 2005) revealed that compounds with 11 carbons in the alkyl substituent showed the most activity against a range of bacteria and fungi.…”
Section: Antimicrobial and Antibiofilm Activities Of Ionic Liquidsmentioning
confidence: 99%
“…However, toxicity itself is a tuneable property which may be of utility in a number of other applications, for example, in the development of antiseptics, disinfectants and anti-fouling reagents [60][61][62][63]. The antimicrobial activities of the choline-like quaternary ammonium chloride ionic liquids were evaluated against a range of Gram positive and Gram negative bacteria [64].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%